Atomically Thin 1T-FeCl2 Grown by Molecular-Beam Epitaxy - Zhou, Xuhan; Brzostowski, Bartosz; Durajski, Artur; Liu, Meizhuang; Xiang, Jin; Jiang, Tianran; Wang, Zhiqiang; Chen, Shenwei; Li, Peigen; Zhong, Zhihao; Drzewiński, Andrzej; Jarosik, Marcin; et al. (Journal of physical chemistry. C, 2020)
Two-dimensional (2D) magnetic materials have attracted much attention due to their unique magnetic properties and promising applications in spintronics. Here, we report on the growth of ferrous chloride (FeCl2) films on Au(111) and graphite with atomic thickness by molecular-beam epitaxy (MBE) and the layer-dependent magnetic properties by density functional theory (DFT) calculations. The growth follows a layer-by-layer mode with adjustable thickness from sub-monolayer to a few layers. Four types of moiré superstructures of a single-layer FeCl2 on graphite and two types of atomic vacancies on Au(111) have been identified based on high-resolution scanning tunneling microscopy (STM). It turned out that the single- and few-layer FeCl2 films grown on Au(111) exhibit a 1T structure. The DFT calculations reveal that a single-layer 1T-FeCl2 has a ferromagnetic ground state. The minimum-energy configuration of a bilayer FeCl2 is satisfied for the 1T–1T structure with ferromagnetic layers coupled antiferromagnetically. These results make FeCl2 a promising candidate as ideal electrodes for spintronic devices providing large magnetoresistance.